Pharmacological significance of biogenic amines in the lungs: Histamine - Aviado, Domingo M. (1970)
1. Eight animal species were investigated for the histamine content of the lung and can be divided into two groups: the low-level group, ranging from 2 to 7 μg/g, consisting of the mouse, rat, guinea-pig and rabbit; and the high-level group, ranging from 12 to 35 μg/g, consisting of the cat, dog, goat and human. In two species of the high-level group (cat and dog) the amount of histamine that elicited an increase in pulmonary resistance was one-fifth to one-tenth of the dose that elicited an increase in species of the low-level group (rat and rabbit). There is an inverse relationship between the content of histamine and the dose of histamine that produces a 25% increase in pulmonary resistance. 2. Anaphylaxis increases the histamine content of the lung of the rabbit but not of the lung of the guinea-pig. In both species, anaphylaxis is accompanied by an elevation of the concentration of 5-hydroxytryptamine in the lung, indicating the trapping of platelets in the lung. 3. The development of severe parasitaemia in the mouse inoculated with Plasmodium berghei is accompanied by an elevation of the histamine content of the lung. This increase appears to be part of the response of the lung to parasitaemia.